Analisis Perilaku Konsumsi Anak Kos Terhadap Makanan Organik Sebagai Investasi Kesehatan Jangka Panjang - Rismayani F, Agis; Syafa C, Andina; Anggieta, Reisha; Putri A, Salsabilah; Cahyaning S, Tiara; Wijaya Abdul Rozak, Rama (Jurnal Sosiologi Pertanian dan Agribisnis, 2023)
Analysis the behavior of boarding children on long-term health. The method used in this study is a quantitative method with interviews. Most boarding children choose instant food over organic food, based on the price of the goods. on the interview data, some boarding children still choose instant food over organic food, it shows that boarding children still choose a low level of long-term health awareness.